2005
DOI: 10.1353/cja.2005.0055
|View full text |Cite
|
Sign up to set email alerts
|

Data Quality in an Information-Rich Environment: Canada as an Example

Abstract: This review evaluates the quality of available administrative data in the Canadian provinces, emphasizing the information needed to create integrated systems. We explicitly compare approaches to quality measurement, indicating where record linkage can and cannot substitute for more expensive record re-abstraction. Forty-nine original studies evaluating Canadian administrative data (registries, hospital abstracts, physician claims, and prescription drugs) are summarized in a structured manner. Registries, hospi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
110
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 167 publications
(112 citation statements)
references
References 74 publications
0
110
0
2
Order By: Relevance
“…The analysis used a population-based cohort approach, including all residents age 40 or older identified in the anonymized administrative data housed at the manitoba Centre for Health Policy. This data system contains complete and validated health service records Age Difference Explains Gender Difference in Cardiac Intervention Rates After Acute Myocardial Infarction for virtually every resident of the province (Roos et al 2005). The Health Research Ethics Board of the university of manitoba approved this study as part of a larger project on gender differences in health and healthcare use (fransoo et al 2005).…”
Section: Methodsmentioning
confidence: 99%
“…The analysis used a population-based cohort approach, including all residents age 40 or older identified in the anonymized administrative data housed at the manitoba Centre for Health Policy. This data system contains complete and validated health service records Age Difference Explains Gender Difference in Cardiac Intervention Rates After Acute Myocardial Infarction for virtually every resident of the province (Roos et al 2005). The Health Research Ethics Board of the university of manitoba approved this study as part of a larger project on gender differences in health and healthcare use (fransoo et al 2005).…”
Section: Methodsmentioning
confidence: 99%
“…The validity and accuracy of these datasets was excellent and had been validated in previous studies [31]. The linkage of these databases was shown to have very high accuracy [32][33][34][35]. For example, the true error rate of an original linkage of deaths reported by Vital Statistics was less than 1% [32].…”
Section: Data Sourcesmentioning
confidence: 68%
“…The data quality of both the NRS and CIHI-DAD is maintained through variable verification, and audit-feedback; reabstraction studies have shown 480% agreement with coding elements. 7 Physician billing occurs through the OHIP, and surgical fee claims are expected to have a high sensitivity and positive predictive value (PPV), as shown with other service payments. 8 Data analysis.…”
Section: Methodsmentioning
confidence: 99%